Behavioral ecology: New technology enables a more holistic view of complex animal behavior - Gail L. Patricelli (PLoS Biology, 2023)
As any animal observer will tell you, behavior is complex. A more holistic view of this complexity is emerging as technological advances enable the study of spatiotemporal variability and expand the focus from single components to behavioral systems. Animal behavior is notoriously complex. This Perspective looks at how technological advances have enabled the study of variability over space and time, enabling a more holistic view of this complexity and expanding the focus from single components to behavioral systems.